Spontaneous Poisoning by Ricinus communis in Sheep - Bianchi, Matheus Viezzer; Vargas, Thainã Piccolo; Filho, Ronaldo Viana Leite; Guimarães, Lorena Lima Barbosa; Heck, Lilian Cardoso; Pavarini, Saulo Petinatti; Driemeier, David (Acta Scientiae Veterinariae, 2018)
Background: Ricinus communis (castor bean) is an arbustive plant, popularly known in Brazil as “mamona”. This plant is widely distributed both as a weed in pastures and in specific cultures. All parts of the plant are poisonous and contain the toxic substance ricin, especially the seeds, leaves and pericarp. The ingestion of leaves and pericarp may cause neurological signs. Gross findings are unspecific, however the main finding is the presence of leaves and seeds in the ruminal content. This report aims to describe the clinical, epidemiological and pathological features of a spontaneous poisoning by R. communis in two sheep. Cases: During the month of March of 2015, six sheep that were kept in a native pasture with high amounts of capimannoni (Eragrostis plana) and received alfalfa hay, had access in the morning to an area infested by R. communis, which was previously cut. Two of these animals presented in the same day at the afternoon clinical signs of apathy, dyspnea and recumbency, followed by death. The inspection of the area infested by R. communis revealed that large amounts of seeds and leaves of this plant were consumed. The two sheep were submitted to necropsy, where multiple samples were collected and processed routinely for histology. Grossly, there were cyanotic mucosae and alimentary content around the nostrils. The ruminal content was dry and showed large amounts of partially digested leaves and seeds. Microscopically, rumen, reticulum and omasum had mild hydropic degeneration in the mucosa, in addition to a mild inflammatory infiltrate composed of lymphocytes and plasma cells. Discussion: The diagnosis of R. communis poisoning in two sheep was obtained through the epidemiological aspects, such as the observation of the plant consumption, in addition to the clinical and pathological features. The observation of digested seeds and leaves in the ruminal content is similar to the previously described in cattle and essential to the diagnosis of the condition, since the gross and microscopic lesions are usually unspecific and mainly characterized by edema and congestion of the digestive tract from the abomasum to the proximal colon. Sheep and cattle poisoned with seeds of R. communis may show gastrointestinal clinical signs mainly. In the present study, however, the clinical course was peracute with only dyspnea and recumbency, suggesting a nervous form of the condition. This form of poisoning is associated to the consumption of dry leaves and clinical signs may be observed within 3-6h after consumption. These are characterized by unbalance walk, muscle tremors, sialorrhea, chewing movements and excessive eructation, and can rapidly progress to death, as in the present study, and in other spontaneous poisoned sheep. The condition should be differentiated from arsenic poisoning, which presents mainly vascular lesions involving the rumen, reticulum and omasum, as well as other poisonings that cause gastroenteritis, such as Baccharis coridifolia poisoning, which culminates with mucosa necrotic lesions involving the pre-stomachs. A high mortality may have occurred due to the food shortage, which in association to the prolonged mastication of ruminants may have increased the ricin release from the seeds and leaves. Ricinus communis poisoning in sheep may occur spontaneously in association with food shortage. The clinical course of these cases may be peracute (neurological form), usually leading to death, with scarse previous clinical signs. The diagnosis of this poisoning should be based on the observation of the previous consumption of the plant, as well as observation of seeds and leaves of the plant intermixed with the ruminal content, since microscopic lesions are rare. Keywords: castor bean, pathology, neurological, sudden death, toxicology.